The Relationship Between Serum 25 hydroxy Vitamin D Deficiency and Dietary Pattern in Baxshin Hospital, Sulaimani City - I M Gubari, Mohammed; Muhamad Abdul Aziz, Jeza; Ahmed Mohialdeen, Fadhil; Anwar Hama-Ghareeb, Khalid; Kamal Muhamed, Bakhtyar; Abdalla Omer, Hemn (Kurdistan Journal of Applied Research, 2018)
Vitamin D is one of the fat-soluble vitamins that have a great role in phosphate and calcium balance and bone structure. To our knowledge, there are limited data on the relation between dietary pattern and serum vitamin d concentration. Therefore, the aim of the current study is find out whether, there are any associations between serum vitamin D and with any specific dietary pattern. A cross sectional study was implemented in Baxshen hospital in order to find the prevalence of vitamin D deficiency and its relation with dietary pattern among healthy participants. 1131 participants were enrolled in the current study male and female with age 18 – 65 years old, living in Sulaimani city and its districts have not used any supplement in the past 6 months before enrolling the study. Two questionnaires were used for collecting of data, the first one was included demographical data of the participants. Including their age, gender, marital status, educational level, address, and etc. The second one was data on dietary pattern; particularly we focused on some vitamin D dietary sources. A three-day dietary records estimate was taken from the patients and this data were coded and put in dietary software (windiet) and then analyzed. The age of the sample ranged from 18 to 65 years old with the mean of 34.34 years old with a standard deviation of 12.6. One hundred sixty-two (14.3%) of the 1131 participants were female, nine hundred sixty-nine (85.7%) of the participants were male. 65.5 % of them exposure to sun less than 30, 34.5% exposure to sun more than half hour. About 84.6% of participants had severe deficiency of vitamin D and 6.9% of participants had adequate vitamin D. Fish, eggs and yogurt conception was common among those participants whom their serum vitamin D was adequate, in contrary, there were less consumed among those who had vitamin D deficiency. The percentage of obese (99.8%) was significantly higher than normal weight and overweight among severe deficiency Vitamin D. Furthermore, a highly percentage of adequate was (93.6%) in the normal weight. The mean of vitamin D intake was 761 ± 195.65 IU, in normal weight group, and the mean of vitamin d intake was 125.98 ± 53.15 IU, in obese group. This study has concluded that the reach Dietary sources of vitamin D is not enough to provide the body adequate amount of vitamin D, in addition, Obese and overweight individuals tend to have less serum vitamin D status compared to normal weight individuals and finally recommended daily amount of vitamin d intake should be established for Kurdistan people.